“White-line” ptosis repair with complications - Suzana Matayoshi; Alice Carvalho Gouveia de Almeida; Silvana Artioli Schellini (2024)
Figure 1.Scleral ulcer in the upper region of the eye, surrounded by dilated conjunctival vessels.